STUDENT CIVIC PARTICIPATION AND SCHOOL CLIMATE: ASSOCIATIONS AT MULTIPLE LEVELS OF THE SCHOOL ECOLOGY. Issue 2 (March 2016) - Karakos, Holly L.; Voight, Adam; Geller, Joanna D.; Nixon, Carol T.; Nation, Maury
Abstract : Research suggests that youth civic participation predicts desirable outcomes for engaged individuals, but less is known about the benefits of individual participation that accrue to schools as a whole. The present study investigates whether students' individual and collective participation predict students' perceptions of school climate. We examine survey and administrative data from 4, 947 students from 11 middle schools. Using multilevel modeling we examine the association of aggregate civic participation at the grade cohort level with school climate. Cohort‐level civic participation has a significant positive association with perceived school climate, specifically student–teacher relationships, the fairness of school rules, and democratic climate. These aggregate associations are estimated over and above individual‐level civic participation, which is independently predictive of school climate. Results demonstrate that students' civic participation is associated with positive individual and setting‐level outcomes, such as positive perceptions of school climate. Limitations of this study and suggestions for future research are discussed.